Perang Cumbok: Konfrontasi dan Perubahan Sosial di Aceh Tahun 1945-1946 - Fatianda, Septian; Suraiya, Suraiya; Al Maududdy, Avicenna; Manan, Abdul (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2024)
The Cumbok incident occurred in Aceh between Ulama and Uleebalang. Since Dutch colonialism, these two groups of people have always been at odds. The Uleebalang group has long been considered to be opposing the struggle of Acehnese ulama and mujahideen fighters against the threat of Dutch colonialism. This background pushed the Cumbok war into a major war which as a result changed the social order of Acehnese society. This research is historical research with a political approach by conducting historical investigations. Examining the events of the Cumbok War and the impact of social change of the war is the research objective. This research methodology is a literature review that utilizes various reference sources. The socio-political situation of Aceh after Indonesian independence, the process of the Cumbok War and an analysis of the impact of the Cumbok War on the transition of Acehnese society will be presented in this article.Â